A long-term mechanical cavopulmonary support device for patients with Fontan circulation. (August 2019) - Granegger, Marcus; Thamsen, Bente; Hubmann, Emanuel J.; Choi, Young; Beck, Dominik; Valsangiacomo Buechel, Emanuela; Voutat, Michael; Schweiger, Martin; Meboldt, Mirko; Hübler, Michael
Highlights: A small long-term cavopulmonary assistance pump for Fontan patients was developed. In-vitro and in-silico evaluations confirmed fulfillment of predefined requirements. Simulations revealed low shear, good washout and low increase of blood temperature. Virtual fitting indicated implantability in a large cohort of Fontan patients. Abstract: In patients with a single ventricle, failure of the cardiovascular system may be prevented by substituting the missing sub-pulmonary ventricle with a pump. The aim of this study was to design and evaluate a device for long-term cavopulmonary support. A radial pump with two inlets and two outlets, a single impeller, mechanical bearings, and dual motor configuration was developed. Motor and fluid dynamic components were designed and simulated using computational methods including thermal effects. Hydraulic properties were determined in-vitro with 3D-printed prototypes. The pump design was virtually implanted in an MRI-derived total cavopulmonary connection (TCPC). Computational fluid dynamics (CFD) showed flow fields without regions of flow stagnation (velocity < 0.1 m/s) and only minor recirculations within the pump between 2–10 L/min against pressure heads of 0–50 mmHg at 2500–5000 rpm. The computed maximum temperature increase of blood due to motor heat was 1.3 K. Virtual implantation studies showed that the pump would introduce an additional volume of approximately 4 mL. Experimentally determined hydraulic performance results agreed well with CFD (deviation of <1.3 mmHg) and indicated pressure-sensitive characteristics (∼-2.6 mmHg/(L/min)) while balancing the two inlet pressures (∆ P  < 2.5 mmHg) under imbalanced inflow conditions. Through in-silico and in-vitro investigations, we demonstrated a promising pump design, which fulfills the basic requirements for long-term cavopulmonary support.